Afonso Lomonaco: a visão de um viajante europeu sobre o Brasil do final do século XIX - OLIVEIRA, Flávia Arlanch Martins de (2007)
This article depicts the views left by the Italian traveller Affonso Lomonaco about Brazil in his book Al Brazile . I show, that, as his itinerary was limited only to places where the railroad served, his accounts about the Brazilian Society were limitary to what he saw in the urban environments. Also, because he was a city born european, his impressions are presented deeply marked by burgeois and racist values.